2022
DOI: 10.3390/biom12030429
|View full text |Cite
|
Sign up to set email alerts
|

Kv7 Channels in Cyclic-Nucleotide Dependent Relaxation of Rat Intra-Pulmonary Artery

Abstract: Pulmonary hypertension is treated with drugs that stimulate cGMP or cAMP signalling. Both nucleotides can activate Kv7 channels, leading to smooth muscle hyperpolarisation, reduced Ca2+ influx and relaxation. Kv7 activation by cGMP contributes to the pulmonary vasodilator action of nitric oxide, but its contribution when dilation is evoked by the atrial natriuretic peptide (ANP) sensitive guanylate cyclase, or cAMP, is unknown. Small vessel myography was used to investigate the ability of Kv7 channel blockers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Moreover, the authors demonstrated the protein expression of Kv7.1 and Kv7.4 proteins in rat pulmonary arteries, and that the selective activation of Kv7.1 and Kv7.4 channels, but not Kv7.5, caused PA relaxation. This study demonstrated that Kv7.4 channels contribute to endothelium-dependent PA relaxation by the cGMP-signaling pathway but have a lesser role in cAMP signaling [ 10 ].…”
mentioning
confidence: 99%
“…Moreover, the authors demonstrated the protein expression of Kv7.1 and Kv7.4 proteins in rat pulmonary arteries, and that the selective activation of Kv7.1 and Kv7.4 channels, but not Kv7.5, caused PA relaxation. This study demonstrated that Kv7.4 channels contribute to endothelium-dependent PA relaxation by the cGMP-signaling pathway but have a lesser role in cAMP signaling [ 10 ].…”
mentioning
confidence: 99%